내도복 저아밀로스 벼 신품종 ‘진상’ - 홍우주(Woo Ju Hong); 윤민영(Min-Young Yoon); 라원희(Won-Hee Ra); 박재완(Jae-Wan Park); 민선경(Sun-Kyung Min); 권순욱(Soon-Wook Kwon); 조유현(Yoo-Hyun Cho); 박용진(Yong-Jin Park) (Korean journal of breeding, 2014)
‘진상’은 공주대학교에서 2013년도에 육성한 고품질 저아밀로스 품종으로 주요특성과 수량성을 요약하면 다음과 같다. 1.‘진상’은 중서부평야 보통기 보비재배에서 출수기가 8월 11일로 ‘추청’보다 약 11일 빠른 중생종으로, 이삭길이는 19 cm로 ‘추청’과 비슷한 수준이었으나, 간장은 75.2 cm로 ‘추청’보다 짧다. 2.‘진상’의 정현비율은 81.2%로 ‘추청’과 비슷한 수준이며 현미길이와 폭이 각각 4.86 mm, 2.91 mm로 ‘추청’에 비해 약간 길고, 넓은 단원형 품종이다. 현미 천립중은 20.91 g 수준이며, 수량성은 457 kg/10a로 ‘추청’과 비슷하였다. 3.‘진상’은 중간찰벼로서 투명도가 중간 정도의 불투명 배유 특성이고, 알칼리 붕괴도는 6.4 정도이며, 아밀로스함량은 11.9%로 대조품종 19.1%보다 낮고, 도요 식미기로 측정한 밥 윤기치는 대조품종인 ‘추청’보다 높게 나타났다. ‘Jinsang’ is a new japonica rice variety was derived from a cross between ‘Yumetsukushi’ as a high grain quality and ‘Milky queen’ with low amylose content and good eating quality in 2000, and selected by pedigree breeding method until M8 generation. As a result, a promising line, JCH33M-15-1-9-1-5-1-1-1, was advanced and designated as the name of ‘HJ-2’in 2009. This variety has about 111 days to heading after sowing and has 75.2 cm culm height. Milled rice of that shows dull and medium short grain and 1,000-grain weight was about 20.9 g. It has low amylose content of 11.9% and lower protein content of 6.8%. The yield potential of ‘Jinsang’ in brown rice was about 4.57 MT/ha by ordinary culture in replicated yield trial test.